A study on communication decision making and dispute resolution in the private sector (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study examining the application of communication, decision making and conflict management in the private sector with special reference to its efficiency. The study how communication tactics can affect decision-making and conflict-solving procedures in private businesses. This study adopted a survey and interview method to gather data from managers and employees from various industries. The study findings show that clear communication greatly improves the decisions making process and minimizes the chances of conflict. The study also shows how decision-making models and ADR methods like mediation and arbitration can be used to promote a positive working culture. The findings call for private sector organizations to enhance the communication and develop effective conflict resolution strategies that can be implemented in the organizations. This research adds to the body of knowledge in the area of organizational behavior by offering a way to enhance communication and conflict resolution to enhance corporate governance and productivity.